2022
DOI: 10.1101/2022.08.06.22278373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure–response relationships for personal exposure to fine particulate matter (PM2·5), carbon monoxide, and black carbon and birthweight: Results from the multi-country Household Air Pollution Intervention Network (HAPIN) trial

Abstract: Background Household air pollution (HAP) from solid fuel use is associated with adverse birth outcomes, but data on exposure-response relationships are limited. We examined associations between HAP exposures and birthweight in rural Guatemala, India, Peru, and Rwanda during the Household Air Pollution Intervention Network (HAPIN) trial. Methods We recruited 3200 pregnant women between 9 and <20 weeks of gestation. Women randomized to the intervention arm received a liquified petroleum gas (LPG) stove and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Meanwhile, the HAPIN study has demonstrated more conclusively than ever that meaningful reductions in household air pollution can be achieved through consistent use of LPG stoves. 22 “We were really pleased to see the proportion of the intervention measurements, about 70%, that were below the WHO Interim 1 standard for fine particulate matter of ,” says Peel. “That’s pretty remarkable, especially compared to previous similar trials that were trying to reduce exposure.”…”
Section: Natural Gas—cleaner Indoor Air In the Interimmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the HAPIN study has demonstrated more conclusively than ever that meaningful reductions in household air pollution can be achieved through consistent use of LPG stoves. 22 “We were really pleased to see the proportion of the intervention measurements, about 70%, that were below the WHO Interim 1 standard for fine particulate matter of ,” says Peel. “That’s pretty remarkable, especially compared to previous similar trials that were trying to reduce exposure.”…”
Section: Natural Gas—cleaner Indoor Air In the Interimmentioning
confidence: 99%
“…In homes that switched from solid fuels to LPG, HAPIN researchers found associations between lower exposures to both and black carbon and higher birthweight and weight-for-gestational-age among babies born to mothers living in those homes, suggesting that using the new stoves may have also meaningfully improved health outcomes. 22 As of February 2023, these results had not yet been peer-reviewed but were available as a preprint.…”
Section: Natural Gas—cleaner Indoor Air In the Interimmentioning
confidence: 99%
“…In a study by Balakrishnan et al, the odds of LBW were found to increase by 2% with a 10 µg m −3 increase in PM 2.5 emitted from solid fuel use in households. A non-linear relationship between PM 2.5 and birth weight (initial increase in birthweight with higher PM 2•5 followed by a subsequent decrease at the higher exposures) was observed in a multicountry randomized clinical trial [16]. Although limited, more recent evidence also raises the possibility of the influence of ambient air pollution (AAP) on the LBW-HAP risk association [17].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to household air pollution ranks among the top risk factors contributing to the global burden of disease and accounted for 2.3 million deaths and more than 90 million disability-adjusted life years (DALYs) in 2019 with disproportionate adverse health effects in low- and middle-income countries (LMICs) . Health outcomes associated with household air pollution include adverse respiratory (acute respiratory infection in both adults and children, chronic obstructive pulmonary disease, and lung cancer), cardiovascular (cerebrovascular disease, ischemic heart disease, and cardiovascular mortality), and birth (low birth weight and small for gestational age) outcomes. …”
Section: Introductionmentioning
confidence: 99%
“… 2 Health outcomes associated with household air pollution include adverse respiratory (acute respiratory infection in both adults and children, chronic obstructive pulmonary disease, and lung cancer), cardiovascular (cerebrovascular disease, ischemic heart disease, and cardiovascular mortality), and birth (low birth weight and small for gestational age) outcomes. 3 11 …”
Section: Introductionmentioning
confidence: 99%